The Deed of Heirs or Obtain rights within The Confidentiality of The Notary's Position - Suprayitno, Suprayitno; Tony, Tony; Alnas, Mujib Medio; Teodoran, Vincent; Nawawi, Vivi Damayanti (Journal of Legal and Cultural Analytics, 2024)
A notary is a public official who has the authority to make authentic deeds and has other authorities as intended in Law no. 2 of 2014 concerning Amendments to Law no. 30 of 2004 concerning Notary Positions (UUJN) and based on other laws. The problem in this paper is how to provide documents by a notary to parties who have a direct interest in the deed, heirs or people who have the right to do so within the confidentiality limits of the notary's office. The notary's authority to provide documents as intended in article 54 UUJN is limited by the notary's obligation to keep it confidential as intended in article 16 paragraph (1) letter f, the exception is if there are statutory provisions that determine otherwise. The party with a direct interest in the deed, on the one hand, is the person who signs the deed in front of a notary or is a party to the deed, and on the other hand, this person is the person who has rights and obligations regarding what is regulated in the deed. Furthermore, those included in the heirs are the heirs of people or parties who have a direct interest in the deed. Meanwhile, a person who is categorized as a person who has rights is a person who has or obtains rights related to what is stated in the deed, although this person or party does not have to be the person who signed the deed.